Rancang Bangun Sistem Informasi dan Pelayanan E-Ticket (Booking Online) pada Wisata Pendakian Gunung Budheg Tulungagung menggunakan Website dengan Framework Laravel - Maysce Christi; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Mount Budheg climbing tourism is one of the popular tours in Tulungagung Regency and has also become an icon in this Regency. On this climbing tour of Mount Budheg, they still carry out their services manually, starting from buying tickets or paying for entrance tickets. This raises problems such as the large number of visitors queuing when they want to enter the Budheg Mountain climbing tour, visitor data collection which will take a long time, and also payments that will be squandered when visitors have very large nominal amounts of money. Based on the description of the problem, the technology design for climbing Mount Budheg was carried out by building an E-Ticketing Information and Service System (Online Booking) by utilizing the Midtrans Payment Gateway. This information system will be designed based on the System Development Life Cycle Method or can be called System Development Life Cycle with the waterfall model. This information system is used by two actors, namely prospective climbers and also the admin. Has functional needs with a total of 13 and 2 non-functional needs. All of these needs will be designed using the Unified Modeling Language (UML), namely use case diagrams, activity diagrams, sequence diagrams, and class diagrams. Next is the database design stage or what can be called the Physical Data Model (PDM) then the interface or system interface design stage. The results of this design will be implemented into programming code with the programming language PHP, HTML, CSS, Javascript, with the Laravel Framework and MySQL database. In the testing process of this research consists of BlackBox testing, Compatibility testing, and Usability testing. BlackBox testing has 13 test scenarios and gets 100% valid test results. Compatibility testing uses a tool called SortSite which has the result that the system can run smoothly in all browsers without losing its functionality. Usability testing has a usability percentage value of 87%, this percentage explains that this e-ticketing or online booking information system can be accepted by users with very decent criteria.